Pengaruh CSR Disclosure terhadap Earning Response Coefficient (Suatu Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Jakarta) - Yosefa Sayekti; Ludovicus Sensi Wondabio (Jurnal Akuntansi dan Bisnis, 2008)
The purpose of the study is to examine the effect of the information of Corporate Social Responsibility disclosed in the companies’ annual reports on the informativeness of earnings (measured by earning response coefficient, ERC). The study hypothesized that there is negative effect of CSR disclosures level on the ERC since the CSR disclosures provide investors more information which is not captured by the accounting earnings. The sample of the study consist of 108 annual reports 2005 of the companies listed at the Jakarta Stock Exchange. The empirical results of the study show that the level of CSR disclosures has negative effect on the ERC as predicted. The results of the study indicate that investors assess the CSR information disclosed by the companies in their annual reports for their investment decision.